Novel Compound Heterozygous Mutations in the TRAPPC9 Gene in Two Siblings With Autism and Intellectual Disability - Hnoonual, Areerat; Graidist, Potchanapond; Kritsaneepaiboon, Supika; Limprasert, Pornprot (Frontiers in Genetics, 2019)
Autism spectrum disorder (ASD) is a highly heterogeneous neurodevelopmental disorder with many contributing risk genes and loci. To date, several intellectual disability (ID) susceptibility genes have frequently been identified in ASD. Here, whole exome sequencing was carried out on a proband with ASD and identified compound heterozygous mutations of the TRAPPC9, which plays a role in the neuronal NF-κB signaling pathway. These mutations consisted of a novel frameshift mutation (c.2415_2416insC, p.His806Profs*9) and a rare splice site mutation (c.3349+1G>A) that were segregated from an unaffected father and unaffected mother, respectively. These two heterozygous mutations were also identified in the patient’s older brother with ID. Quantitative RT-PCR revealed a significant reduction of TRAPPC9 transcript in two siblings. This study first describes compound heterozygous mutations of the TRAPPC9 gene in two siblings with ASD and ID, which is notable as only homozygous mutations or compound heterozygous for copy number variations and rare variant in this gene have been reported to date and associated with autosomal recessive intellectual disability. The two siblings carrying compound heterozygous TRAPPC9 mutations presented with ID, developmental delay, microcephaly and brain abnormalities similarly to the clinical features found in almost cases with homozygous TRAPPC9 mutation in previous studies. Together this study provides evidence that clinical manifestations of TRAPPC9 mutations as seen in our patients with ID and autism may be broader than previous case reports have indicated.